CLAIMING ‘RIGHTS’ IN THE AFRICAN CITY: POPULAR MOBILISATION AND THE POLITICS OF INFORMALITY IN NAIROBI, RABAT, JOHANNESBURG AND CAPE TOWN. - Benit-Gbaffou, Claire; Oldfield, Sophie (Oxon & New York. Routledge, 2014)
In this chapter however, we do not directly use the term ‘right to the city’, as we follow Mayer (2009) in her call against the ‘proliferation of this rights [to the city] discourse’ that runs the risk of weakening its political power (see also Purcell 2002)....Our aim, in articulating urban mobilisation to the notion of ‘rights’ (in the plural) in this chapter, is to understand more narrowly, more practically, and perhaps then theoretically, to what extent these ‘rights’ to the city are (or not) a strategic tool for collective mobilisation in cities of the South to access urban goods, spaces, resources. In this respect, we are more interested in literature that takes the notion of ‘rights’ seriously, in line with Fernandez in Brazil (2007) or Bhan in India (2009) for instance: examining the legal dimension of ‘rights’ and its impacts in securing different forms of access to urban spaces and urban goods. But this approach needs to explicitly take into account how the formality of this definition unfolds in urban politics and collective mobilisation marked by high levels of informality.
The groundswell of mass popular activism in contemporary cities –in particular in the global South- has (re)inspired an academic literature on ‘the right to the city’ (Purcell 2002; Brenner, Marcuse and Mayer 2012; Harvey 2012; Schmid 2012; Samara et al. 2013), and has crystallised the emergence of global social movements claiming a ‘right to the city’ (Purcell 2003; Portaliou 2006, Mayer 2009), more or less rooted in localised political initiatives (see Fernandes 2007 for the Brazilian case for instance). Whilst both academics and activists do not necessarily directly nor even implicitly refer to Lefebvre’s initial concept of the ‘right to the city’ (Mayer 2009), and are rather developed in articulation with dynamics of urban neoliberalisation (Harvey 2008, Brenner et al. 2012), it could be argued that they both are calling for ‘some kind of [radical and fundamental] shaping power over the processes of urbanization, over the ways in which our cities are made and remade’ (Harvey 2012: 5).
Keywords: Global South; Cities; African City; Rights to the City; politics of Informality; Nairobi, Johannesburg; Cape Town.